2020
DOI: 10.1177/0961203320950477
|View full text |Cite
|
Sign up to set email alerts
|

Antiphospholipid syndrome (APS) in patients with systemic lupus erythematosus (SLE) implies a more severe disease with more damage accrual and higher mortality

Abstract: Introduction Antiphospholipid antibodies (aPL) have been associated with organ damage and certain features in systemic lupus erythematosus(SLE) patients. Our aim was to investigate the differences between SLE patients according to the presence of aPL and/or clinical antiphospholipid syndrome (APS). Materials and methods Patients from the RELESSER-T registry were included. RELESSER-T is a Spanish multicenter, hospital-based, retrospective, SLE registry. Results We included 2398 SLE patients, 1372 of whom were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 45 publications
4
7
0
Order By: Relevance
“…Our results are in line with Riancho-Zarrabeitia et al who found that antiphospholipid syndrome in patients with systemic lupus erythematosus predicts a more serious disease with higher accrual damage and higher mortality rates [ 35 ].…”
Section: Discussionsupporting
confidence: 92%
“…Our results are in line with Riancho-Zarrabeitia et al who found that antiphospholipid syndrome in patients with systemic lupus erythematosus predicts a more serious disease with higher accrual damage and higher mortality rates [ 35 ].…”
Section: Discussionsupporting
confidence: 92%
“…(32,34,39) Second, the presence of aPL has been linked to NP-SLE but also to greater damage accruals and mortality in our cohort. (40) However, in our study, CVD was identified as a predictor of mortality independently of the effect of other severe SLE involvement such as lupus nephritis and the presence of APS, which were also accounted for in the models. Furthermore, the same findings were found after the inclusion of comorbidities and the use of glucocorticoids in the model.…”
Section: Discussionmentioning
confidence: 56%
“…Compared with patients diagnosed as having primary APS, patients with APS as well as an SLE history presented increased incidences of arthralgias and arthritis, leukopenia, autoimmune hemolytic anemia, livedo reticularis, epilepsy, and myocardial infarction [ 17 ]. Furthermore, those patients exhibited higher rates of hypertension, dyslipidemia, diabetes, and severe lupus profiles with major organ involvement and higher rates of mortality [ 10 , 49 ]. Their conditions required long-term anticoagulant treatment and immunosuppressive therapy, including high-dose corticosteroids, cyclophosphamide, and azathioprine [ 50 ].…”
Section: Discussionmentioning
confidence: 99%